Aplication from social projection and community outreach from system engineering curriculum - Rico Bautista, Dewar; Rosado Gómez, Alveiro (Universidad Francisco de Paula Santander, 2016)
This paper describe the Systems Engineering curriculum contributions in the development of social projection and community outreach with productive sectors from local, national and international level. Exist many needs met for computer using since knowledge specific of the science. The results correspond to one innovative strategy that seeks the gradual increase in the appropriation of TIC use, improving the technological infrastructure of the region and the development of applications that integrate processes and people. This proposal stems from the implementation of a self-assessment process as a permanent reflection and obtaining timely and effective information for decision-making in favor of continuous improvement, strengthening the program and the sustainable UFPSO development.